AN EMPIRICAL STUDY ON ASSESSMENT OF TREND ANALYSIS: FOOD GRAIN PRODUCTION IN INDIA - chesneau, christophe; Polisetty, Kalpana; Paltati, Gowthami; Paidipati, Kiran Kumar (Journal of Agricultural Sciences (Belgrade), 2023)
Considering the importance of the food grains to be specified—rice, wheat, coarse cereals, and pulses—is vital in developing the Indian economy. This paper carries out change point detection and trend analysis for the annual historical series of food grains in India. The change points are identified by the methods of Pettitt’s test (PT), Buishand’s Range Test (BRT), and the Standard Normal Homogeneity Test (SNHT). The Mann-Kendall (MK) test is used to know the presence and absence of trends in food grain production, and their slopes are assessed by Sen’s slope estimator. The change point analysis result shows significant change points for food grains at a 95% level. The discrete change points are observed from 1982 to 2009, but the ideal change point, i.e., 1987, is captured in all food grains. In India’s history, agricultural production in the year 1987 was vulnerable due to drought, and thus it is strong evidence of the need to consider methods that are well proven facts. The MK test results reveal that the production of food grains trends are statistically significant and have an upward direction after 1987 in all three segmentation periods.